Assimilation of humidity and temperature observations retrieved from ground‐based microwave radiometers into a convective‐scale NWP model1. (8th August 2016) - Caumont, Olivier; Cimini, Domenico; Löhnert, Ulrich; Alados‐Arboledas, Lucas; Bleisch, René; Buffa, Franco; Ferrario, Massimo Enrico; Haefele, Alexander; Huet, Thierry; Madonna, Fabio; Pace, Giandomenico
Abstract : Temperature and humidity retrievals from an international network of ground‐based microwave radiometers (MWRs) have been collected to assess the potential of their assimilation into a convective‐scale numerical weather prediction (NWP) system. Thirteen stations over a domain encompassing the western Mediterranean basin were considered for a time period of 41 days in autumn, when heavy precipitation events most often plague this area. Prior to their assimilation, MWR data were compared to very‐short‐term forecasts. Observation‐minus‐background statistics revealed some biases, but standard deviations were comparable to that obtained with radiosondes. The MWR data were then assimilated in a three‐dimensional variational data assimilation system through the use of a rapid update cycle. A first set of four different experiments were designed to assess the impact of the assimilation of temperature and humidity profiles, both separately and jointly. This assessment was done through the use of a comprehensive dataset of upper‐air and surface observations collected in the framework of the HyMeX programme. The results showed that the impact was generally very limited on all verified parameters, except for precipitation. The impact was found to be generally beneficial in terms of most verification metrics for about 18 h, especially for larger accumulations. Two additional data‐denial experiments showed that even more positive impact could be obtained when MWR data were assimilated without other redundant observations. The conclusion of the study points to possible ways of enhancing the impact of the assimilation of MWR data in convective‐scale NWP systems.